A walk to remember - Sparks, Nicholas (New York, NY : Grand Central Pub., 2012)
Landon Carter never thought he would fall for Jamie Sullivan, the shy daughter of the town's Baptist minister who showed him the joy and pain of living"--P. [4] of cover.
Student guide includes ELA common core state standards alignment ; critical thinking and comprehension skills development ; SAT/ACT style questions to help students improve test scores ; sample essays with rubric to facilitate writing development and skills. --front cover.
PB
Keywords: Sparks, Nicholas -- Study and teaching; Children of clergy -- Fiction; Teenage boys -- Fiction; Beaufort (N.C.) -- Fiction